О времени исчезновения пеструшки степной на Правобережье Украины - Пидопличко, И.Г. (Вестник зоологии, 1973)
The author reports on the finding of subfossil remains (cranium) of Lagurus lagu¬rus P a l l, in the village of Kosyakovka (Tarashcha district, Kiev region) 300 km to the west of the boundary of its modern area of distribution. He also considers that this animal died out in the Right aBnki Ukraine at the end of the 19th — beginning of the 20th centu¬ries under the influence of anthropical factors (ploughing up of virgin areas, disturbance of biocenotic relations).